Short Communication: Characterization of phenotypic and genotypic antibiotic resistance patterns in Escherichia coli isolates from bloodstream infections - CONNY RIANA TJAMPAKASARI; LANY STEVINA; RAFIKA INDAH PARAMITA (Society for Indonesian Biodiversity, 2026)
Abstract. Tjampakasari CR, Stevina L, Paramita RI. 2026. Short Communication: Characterization of phenotypic and genotypic antibiotic resistance patterns in Escherichia coli isolates from bloodstream infections. Biodiversitas 27 (3): d270320. https://doi.org/10.13057/biodiv/d270320. Extraintestinal pathogenic Escherichia coli (ExPEC) is a leading cause of bloodstream infections (BSIs) worldwide and contributes substantially to the burden of antimicrobial resistance. The aim of this study was to evaluate the concordance between phenotypic antimicrobial susceptibility testing (AST) and genotypic resistance determinants identified by whole-genome sequencing (WGS) in E. coli BSI isolates. During the study period, 194 blood culture samples from patients with suspected BSIs were processed, of which 92 yielded positive results; 13 non-duplicate E. coli isolates (14.13% of positive cultures) were included in this single-center, exploratory study. Phenotypic resistance profiles were determined using the VITEK®2 Compact system, while WGS was performed to identify antimicrobial resistance genes, sequence types (STs), and resistance-associated mutations. Phenotypic resistance showed that resistance to ampicillin (7/13, 53.8%), ciprofloxacin (6/13, 46.2%), and ceftriaxone (5/13, 38.5%). Genomic analysis revealed β-lactam resistance genes predominantly associated with blaTEM-1B and its variants (blaTEM-116, blaTEM-141, and blaTEM-206), along with blaCTX-M-55; blaTEM-1B was the most frequently detected gene (4/13), followed by blaCTX-M-55 (2/13). Fluoroquinolone resistance was mainly linked to mutations within quinolone resistance-determining regions of gyrA and parC, as well as alterations affecting the AcrAB-TolC efflux system. Multilocus sequence typing using the Achtman scheme demonstrated high genetic diversity, with 12 distinct STs identified among 13 isolates, including ST73, ST117, ST410, ST95, and ST127. High concordance between phenotypic β-lactam resistance and genotypic findings was observed, as all β-lactam-resistant isolates carried at least one corresponding β-lactamase gene. Overall, these findings indicate that WGS can reliably confirm β-lactam resistance mechanisms and provide useful molecular epidemiological insights into E. coli isolates causing BSIs; however, conclusions are limited by the small sample size and single-center design, and larger multicenter studies are warranted to support routine surveillance applications.